Grenada report card. - BROTHERSON, Festus, Jr. (1994)
Claims that ten years after US intervention, Grenada has failed in its search for development, and the native culture has become more fragile in light of the penetration of American values and practices. Concludes that it is unlikely that the country can make significant gains in the future.